(untitled) (Zoological Records and Reviews, 2025)
Zoological research – encompassing systematic taxonomy, population ecology, behavioural science, conservation biology, and wildlife management – contributes to sustainable development through multiple pathways: providing the biodiversity knowledge base essential for ecosystem service valuation and natural capital accounting; informing wildlife-based economic sectors (ecotourism, sustainable fisheries, pollination services); enabling zoonotic disease surveillance and pandemic prevention through wildlife health monitoring; supporting food security through insect pollinator conservation and biological pest control research; and generating the evidence base for biodiversity-inclusive land use planning and environmental impact assessment. This review synthesises evidence from 186 primary studies (2005-2025) examining the contributions of zoological research to eight Sustainable Development Goals (SDGs) – SDG 2 (Zero Hunger), SDG 3 (Good Health), SDG 8 (Decent Work), SDG 11 (Sustainable Cities), SDG 13 (Climate Action), SDG 14 (Life Below Water), SDG 15 (Life on Land), and SDG 17 (Partnerships) – quantifying economic and social co-benefits where evidence is available. Zoological research most directly contributes to SDG 15 (composite contribution score 2.72/3.0) and SDG 14 (2.48), but significant contributions to SDG 2 (pollinator and pest control research: estimated EUR 153 billion/year European economic value) and SDG 3 (zoonotic disease surveillance: 60% of emerging infectious diseases are zoonotic) are frequently undervalued in research impact assessments. A framework for aligning zoological research priorities with SDG targets and EU Biodiversity Strategy 2030 commitments is presented.